Neuroimaging and Psychosocial Addiction Treatment An Integrative Guide for Researchers and Clinicians - Feldstein Ewing, Sarah W.; Witkiewitz, Katie; Filbey, Francesca M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Using an innovative translational approach between the work of experimental scientists and clinical practitioners this book addresses the current, modest, understanding of how and why addiction treatment works. Through bridging this gap it provides a critical insight into why people react as they do in the context of addiction treatment.
Keywords: Clinical psychology; Neurosciences; Social policy; Biological psychology; Public health; Psychology, Pathological; Clinical Psychology; Neurosciences; Social Policy; Biological Psychology; Public Health; Psychopathology